2016
DOI: 10.1109/tpel.2015.2512923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Results of Accelerated Aging Tests in Insulated Gate Bipolar Transistors

Abstract: The introduction of fully electric vehicles (FEVs) into the mainstream has raised concerns about the reliability of their electronic components such as IGBT. The great variability in IGBT failure times caused by the very different operating conditions experienced and the stochasticity of their degradation processes suggests the adoption of condition-based maintenance approaches. Thus, the development of methods for assessing their healthy state and predicting their remaining useful life (RUL) is of key importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The open literature on accelerated aging tests in IGBT shows a variety of aging processes, where it was concluded by T c , I c , and V ce characteristics providing a good framework for the PHM process 26–28 . Mainly, we claim that the T c changes its waveform with degradation as it is shown in Figure 7.…”
Section: Igbt Aging Experiments System and Data Recordingmentioning
confidence: 69%
See 1 more Smart Citation
“…The open literature on accelerated aging tests in IGBT shows a variety of aging processes, where it was concluded by T c , I c , and V ce characteristics providing a good framework for the PHM process 26–28 . Mainly, we claim that the T c changes its waveform with degradation as it is shown in Figure 7.…”
Section: Igbt Aging Experiments System and Data Recordingmentioning
confidence: 69%
“…The specifications of the investigated IGBTs under healthy operating conditions are presented in Table 1. For more detailed information about this experiment, interested readers shall refer to References 25–27.…”
Section: Igbt Aging Experiments System and Data Recordingmentioning
confidence: 99%
“…To this end, numerous lifetime models of power electronic devices have been developed. They can be divided in three categories: empirical models [6][7][8], physics-based models [9][10][11][12][13][14][15][16][17][18] and datadriven or stochastic models [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] used the Cauer thermal network model to monitor the temperature change, but it is difficult to obtain the parameters of the model. Astigarrag et al [18] performed power thermal cycling tests on different types of parameter and showed that the case temperature, the collector current and the collector-to-emitter voltage can all be used as failure precursors for prediction and health monitoring. Hence, this study considers the case temperature as the precursor of the fault, which does not take account of the influence of the parameters, such as the collector-to-emitter voltage on the case temperature, so the prediction results have a certain error.…”
Section: Introductionmentioning
confidence: 99%